2022
DOI: 10.1111/bcp.15591
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of pharmacogenomics: Where are we now?

Abstract: Pharmacogenomics (PGx), examining the effect of genetic variation on interpatient variation in drug disposition and response, has been widely studied for several decades. However, as cost, as well as turnaround time associated with PGx testing, has significantly improved, the use of PGx in the clinical setting has been gaining momentum. Nevertheless, challenges have emerged in the broader clinical implementation of PGx. In this review, we will outline current models of PGx delivery and methodologies of evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 199 publications
0
9
0
Order By: Relevance
“… 35 Efficacy to approved drugs varies from 25% to 80%, 35 with increasing evidence that genetic variation plays a role in the efficacy of a given drug in each individual. 35 , 36 , 37 In the present study, the analysis of genes shown to play a role in AAV-mediated gene transfer and expression demonstrates that this may also be the case for AAV gene therapy. Like other drugs, AAV gene therapies have been associated with variable responses despite administration by the same route and dose adjusted to the physical characteristics of the recipient.…”
Section: Discussionmentioning
confidence: 51%
“… 35 Efficacy to approved drugs varies from 25% to 80%, 35 with increasing evidence that genetic variation plays a role in the efficacy of a given drug in each individual. 35 , 36 , 37 In the present study, the analysis of genes shown to play a role in AAV-mediated gene transfer and expression demonstrates that this may also be the case for AAV gene therapy. Like other drugs, AAV gene therapies have been associated with variable responses despite administration by the same route and dose adjusted to the physical characteristics of the recipient.…”
Section: Discussionmentioning
confidence: 51%
“…Establishing or updating well-defined regulations will ultimately force insurance companies to revise their coverage plans to enable PGx testing. A success story is the experience of genotyping for DPYD variant alleles upon fluoropyrimidines prescribing whereby the resulting clinical and economic benefits led to securing governmental financial support in Ontario, with further evidence of cost-effectiveness probably leading to expansion of the experience to other medical institutions ( Brooks et al, 2022 ; Medwid and Kim, 2022 ; Varughese et al, 2022 ). Moreover, the EMA recommended testing for DPYD, but concerns regarding the economic benefit and cost-effectiveness of testing resulted in slow adoption of the recommendation.…”
Section: Stakeholders Engaged In the Clinical Pgx Design And Implemen...mentioning
confidence: 99%
“…Consequently, a list of drugs was suggested by several investigators as ready to be implemented. This list includes but is not limited to: statins, clopidogrel, and warfarin for cardiovascular diseases, codeine and tramadol as opioid analgesics, ondansetron and proton pump inhibitors for gastrointestinal illnesses, fluoropyrimidines, tamoxifen, and thiopurines for cancer, and antidepressants such as the selective serotonin reuptake inhibitors ( Weitzel et al, 2019 ; Rollinson et al, 2020 ; Medwid and Kim, 2022 ). Finally, a fourth study evaluated the longitudinal exposure in primary care in the United Kingdom of a list of 63 drugs identified from the PharmGKB database to be associated with 19 pharmacogenes.…”
Section: Design Of Clinical Pgx In the Hospital Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…Fundamental to the development of genomic medicine is accurate knowledge regarding the disease pathogenesis and acknowledging the genetic contributions to variation in how patients respond to treatment [ 7 ]. Genetic variation among patients modulates drug efficiency and can impose toxic effects (adverse drug reactions) [ 8 ]; thus, understanding how genetic variation affects drug response is essential for the development of genomic medicine.…”
Section: Introductionmentioning
confidence: 99%